Design and implementation of an improved sinusoidal controller for a two-phase enhanced impedance source boost inverter. (May 2020) - Ghaderi, Davood; Padmanaban, Sanjeevikumar; Maroti, Pandav Kiran; Papari, Behnaz; Holm-Nielsen, Jens Bo
Abstract: This study presents a novel Sinusoidal Pulse Width Modulation (SPWM) model for a two-phase Impedance Source-based Inverter (ZSI) with a hardware prototype implementation. The high-gain feature is investigated based on an innovative mathematical model that involves fewer components and presents efficient performances. The presented topology can be applied broadly in Photo Voltaic systems, Wind Power, Fuel Cell, and Uninterrupted Power Supply topologies due to the ability of wide-range load regulation with higher duty cycles. Through Shoot (TS) and higher Total Harmonic Distortion (THD) problems can be solved by a carefully designed gate-drive circuit and proper switching frequency for the appropriate resistance against the Electromagnetic Interfaces (EMIs). One of the essential specifications of the proposed controller is working with intermediate values of duty cycles for power MOSFETs that can decrease the losses for the inverter. A set of numerical simulation and hardware results are presented for ensuring the proposed claims. Graphical abstract: General topology for the proposed method. Image, graphical abstract